am Horizont. - Heynen, Julian (Krefeld : Kaiser Wilhelm Museum, 1999)
Tuymans, Luc ; Schneider, Gregor ; Rhoades, Jason ; Deacon, Richard ; Weigand, Hans ; Mucha, Reinhard ; Fritsch, Katharina ; Schütte, Thomas ; Ahtila, Eija-Liisa ; Huws, Bethan ; Wall, Jeff ; Slominski, Andreas
biografie
am Horizont, Kaiser Wilhelm Museum, Krefeld, 21 november 1999 - 27 februar 2000
Duits
boek